PEMBELAJARAN MENULIS EKSPOSISI BAHASA JAWA RAGAM KRAMA: STUDI KASUS PADA SISWA KELAS X A SMA MUHAMMADIYAH 5 KARANGANYAR - Rosita, Desi; Rakhmawati, Ani; Anindyarini, Atikah (Universitas Sebelas Maret, 2017)
This research aims at describing: 1) the perception teacher of learning writing expository; 2) the planning of writing exspository teaching learning; 3) the implementation of learning writing expository; 4) the obstacles in writing exspository teaching learning; and 5) the effort of solving problems in writing expository teaching learning. The method used is qualitative descriptive method. The sources of data include places and event, informants, and documents. The data collecting technique was conducted through observation, interview, and document analysis. Data triangulation and method triangulation were used in data validity test. Data analysis technique applied interactive analysis model. The researches result showed that: 1) the teacher perception of learning writing expository by theories and practice; 2) the planning of the writing expository teaching was prepared in line with that made by MGMP at Regency level; 3) the implementation of writing expository was conducted by lecturing method and humor strategy; 4) the obstacles faced in learning writing expository are: a) infrastructure haven't been optimally provided; b) the studenst got difficulties in writing essay; c) the students are less active in learning; d) students difficult to choose word in speech level krama; e) limited time; f) the lower participation of students caused monotone of learning; 4) there were some ways to overcome the problems: a) providing sufficient infrastructure at schools; b) giving additional tasks to write at home; c) giving more question to students of learning writing expository; d) the students making a structure text before to applicated in paragraph expository; e) the teacher used the time very well; f) the teacher used a humor strategy of learning writing expository.